Treadmill exercise within lower body negative pressure protects leg lean tissue mass and extensor strength and endurance during bed rest. Issue 15 (5th August 2016) - Schneider, Suzanne M.; Lee, Stuart M. C.; Feiveson, Alan H.; Watenpaugh, Donald E.; Macias, Brandon R.; Hargens, Alan R.
Abstract: Leg muscle mass and strength are decreased during reduced activity and non‐weight‐bearing conditions such as bed rest (BR) and spaceflight. Supine treadmill exercise within lower body negative pressure (LBNPEX ) provides full‐body weight loading during BR and may prevent muscle deconditioning. We hypothesized that a 40‐min interval exercise protocol performed against LBNPEX 6 days week −1 would attenuate losses in leg lean mass (LLM), strength, and endurance during 6° head‐down tilt BR, with similar benefits for men and women. Fifteen pairs of healthy monozygous twins (8 male and 7 female pairs) completed 30 days of BR with one sibling of each twin pair assigned randomly as the non‐exercise control (CON) and the other twin as the exercise subject (EX). Before and after BR, LLM and isokinetic leg strength and endurance were measured. Mean knee and ankle extensor and flexor strength and endurance and LLM decreased from pre‐ to post‐BR in the male CON subjects ( P  < 0.01), but knee extensor strength and endurance, ankle extensor strength, and LLM were maintained in the male EX subjects. In contrast, no pre‐ to post‐BR changes were significant in the female subjects, either CON or EX, likely due to their lower pre‐BR values. Importantly, the LBNPEX countermeasure prevents or attenuates declines in LLM as well as extensor leg strength and endurance. Individuals who are stronger, have higher levels of muscular endurance, and/or have greater LLM are likely to experience greater losses during BR than those who are less fit. Abstract : The effectiveness of exercise against lower body negative pressure to maintain leg lean mass and strength was evaluated during 30 days of bed rest in male and female identical twins. This aerobic exercise maintained leg lean mass and extensor, but not flexor, strength and endurance. Women had smaller changes than men due to their lower pre‐bed rest values. The use of monozygous twins improved the power of many of our statistical comparisons.